The inheritance right of the child conceived by artificial reproduction after the death of the parent (Research, Society and Development, 2022)
The subject of this article is the legal and social consequences of using the technique of artificial human reproduction after the death of the parent. The following problem was investigated: is the hereditary succession of the child conceived after the death of his father possible? The following hypothesis was considered: the legislative omission does not authorize the adoption of the interpretation that generates the distinction between children, regardless of the form of conception, in respect of the dignity of the human person and equality between children. The general objective is to verify the current position on the problem from the various debates related to inheritance law in the face of the absence of sufficient discipline on artificial reproduction after the death of the parent. The specific objectives are: to investigate the constitutional and legal provisions on hereditary, legitimate and testamentary succession in Brazil. This work is important for the operator of the Law due to the importance and details of the subject in the professional performance. For science it is relevant because it contributes to discussions about the legal uncertainty of the subject. It contributes to society, as assisted reproduction is a technique in increasing use, with broad legal and social consequences that require legislative attention. This is theoretical qualitative research with a duration of four months.